Diagnostics of Cutting Tool Condition at Lathes with Numerical Programmed Control in N on-Stationary Formation Modes - I. A. Kashtalyan; P. K. Jukovskiy (Наука и техника)
The paper considers the method which makes it possible to evaluate wear intensity and determine ultimate wear condition of a cutting tool at lathes with numerical programmed control by changes in entropy coefficient of the size stability of machined parts. The system of tool diagnostics and some results of the experimental investigations are given in the paper.